Rodzina miejscem wychowania w traktacie pedagogicznym O wychowaniu dzieci św. Jana Chryzostoma - Uciecha, Andrzej (Śląskie Studia Historyczno-Teologiczne, 1987)
The article discusses the problem of home upbringing in incipient Christianity. Christianity in its beginnings was confronted with the Greek model that was shaped trough ages of experience. It seemed that the new religion would quickly work out a new pedagogic alternative for the output of Hellenistic culture. The old principles of pagan paideia should deifinitely been rejected as hostile and destructive to the evangelical formation of man. Was it so in reality? With an analytical and comparative method the vision of pedagogy in the family home was reconstructed on the grounds of a pedagogic treatise written at the end of 4th century — De educandis liberis Its author is John Chrysostom, an eminent moralist and pedagogue educated on Hellenism. The presentation of his idea of upbringing is the starting point in the discussion on his originality i.e. the degree of dependence upon Greek pedagogy. It should be said here that Chrysostom's model is not very original and is a Christian adaptation of classic traditions. His dependence upon the Greek conception has a formal character. The proper process of upbringing begins at the age of seven. The child is mainly being shaped in the family home. Both parents, but mainly the father, watch over the entire process. The main purpose of upbringing is salvation. Chrysostom forbids punishment in the form of beating and advises reading the Bible; he makes great demands on the father and the domestics. Personal experience, Greek form and Christian contents are the three pillars of his programme. Most probably for Chrysostom it was not a matter of elaborating an innovatory pedagogic system but only of indicating how to increase the knowledge on the traditional model and adapt it to Christianity.